Carbon Materials as Additives to WO3 for an Enhanced Conversion of Simulated Solar Light - Carmona, Rocio J.; Velasco, Leticia F.; Laurenti, Enzo; Maurino, Valter; Ania, Conchi O. (Frontiers in Materials, 2016)
We have explored the impact of the incorporation of nanoporous carbons as additives to tungsten oxide on the photocatalytic degradation of two recalcitrant pollutants: rhodamine B (RhB) and phenol, under simulated solar light. For this purpose, WO3/carbon mixtures were prepared using three carbon materials with different properties (in terms of porosity, structural order and surface chemistry). Despite the low carbon content used (2 wt.%), a significant increase in the photocatalytic performance of the semiconductor was observed for all the catalysts. Moreover, the influence of the carbon additive on the performance of the photocatalysts was found to be very different for the two pollutants. Carbon additives of hydrophobic nature increased the photodegradation yield of phenol compared to bare WO3, likely due to the higher affinity and stronger interactions of phenol molecules toward basic nanoporous carbons. Oppositely, the use of acidic carbon additives led to higher RhB conversions due to increased acidity of the WO3/carbon mixtures and the stronger affinity of the pollutant for acidic catalyst’s surfaces. As a result, the photooxidation of RhB is favored by means of a coupled (photosensitized and photocatalytic) degradation mechanism. All these results highlight the importance of favoring the interactions of the pollutant with the catalyst’s surface through a detailed design of the features of the photocatalyst.